Системи суттєво нескінченновимірних диференціальних рівнянь - Статкевич, В.М. (Український математичний журнал, 2011)
Исследуются системы дифференциальных уравнений с существенно бесконечномерными эллиптическими операторами (типа Лапласа – Леви). Для нелинейных систем доказаны теоремы существования и единственности, для линейной системы приведена явная формула решения. We investigate systems of differential equations with essentially infinite-dimensional elliptic operators (of the Laplace–Lévy type). For nonlinear systems, we prove theorems on the existence and uniqueness of solutions. For a linear system, we give an explicit formula for the solution.